Miscarriages of Justice in Chinese Capital Cases - Miao, Michelle (2018)
In recent years, the media exposure and judicial exoneration of wrongfully convicted defendants in a number of high-profile capital cases in China have attracted the attention of reformers, the general public, and policy makers—both domestic and international. Yet, until now, there has been merely a thin body of empirical literature on this salient research topic. This lack of academic attention is due to the political sensitivity of the topic and the lack of publicly-accessible data. This paper is aimed at filling this critical gap in the literature. Based on in-depth analysis of 122 deathsentenced innocents, of which 109 have been exonerated and five have been wrongly executed, the research findings reveal that: first, murder and robbery account for the majority of convictions; second, over half of those wrongfully convicted were sentenced to the death penalty with immediate execution; (c) third, innocent prisoners facing capital proceedings, on average, were incarcerated 3161.3 days as a result of recursive trials; (d) courts are reluctant to exonerate the innocents, only 4.1% of cases were acquitted in the second instance while 93.44% of those cases were sent to the first instance for retrial, or upheld and sentence reduction at the second instance; (e) there has been a significant reduction in death penalty with immediate execution and increasing in exoneration since 2007. The paper demonstrates that ‘hard strike’ campaigns and provincial higher courts’ review of capital cases bred lethal errors, but China has made great progress in the prevention and correction of wrongful death sentences